The constant-head-orifice farm turnout - Kruse, E. G., author; U.S. Department of Agriculture, Agricultural Research Service, publisher (Colorado State University. Libraries, 1965)
The constant-head-orifice turnout, a structure used for the control and measurement of irrigation water, was calibrated and evaluated in the laboratory. The effects on discharge of sediment, high canal velocities, varying downstream water levels and plugging of the orifice gate by debris were studied. The structure provided reasonably accurate measurement of discharge under most operating conditions. However, when the gate opening was obstructed with debris or when the tail water level was increased, discharges were much less than indicated by the calibration curve. For large discharges, the staff gages furnished erratic indications of the differential head on the orifice gate.
CER65EGK47.
January 1965.
Keywords: Irrigation water; Irrigation -- Management